The ‘Forum Romanum’ and the social education of the ’vir bonus’: the case of Gaius Octavius (I BC) - Campos, Carlos Eduardo da Costa (Romanitas - Revista de Estudos Grecolatinos, 2014)
Studies about the forum feature multiple readings in regard to their meanings for the Romans. After all, certain places may be used throughout history to justify processes of power legitimation, identity construction, as well as segregation or integration between subjects within a segment or in an external environment. The perspective presented here consists in examine the forum as an anthropological place in the educative process of the male young aristocrat in Rome, as Gaius Octavius, so that this subject could become the vir bonus (good citizen) par excellence.